Rupture, Leakage, and Reconstruction: The Body as a Site for the Enforcement and Reproduction of Sex-Based Legal Norms in the Breast Implant Controversy - Bloom, Anne (Columbia Journal of Gender and Law, 2005)
“When is a man a man, and when is a woman a woman?” So asked the Texas Court of Appeals when confronted with a case involving a post- operative transsexual who sought to recover under the state’s wrongful death statute for the death of her spouse, to whom she had been married for seven years. Christie Littleton had been born Lee Cavazos, Jr., a “physically healthy male.” But, at the age of twenty-seven, Christie underwent sex assignment surgery and became an anatomical female. About ten years later, she married Jonathon Littleton and lived with him until his death in 1996. After he died, Christie filed a medical malpractice claim against her husband’s doctor in her capacity as the surviving spouse. The doctor argued, however, that the case should be dismissed because Christie was not a “real” woman and therefore could not be the surviving spouse of Jonathon Littleton. The trial court agreed and entered summary judgment for the doctor. On appeal, the court noted that since Texas did not recognize marriages between persons of the same sex, the key question before the court was: “Is Christie a man or a woman?” In attempting to answer this question, the court acknowledged that Christie currently had the “anatomical and genital features” of a female and that she had “the capacity to function sexually as a female.” The court also acknowledged that many physicians would consider her a female. For the court, however, the most important question was not what Christie looked like now but whether Christie was “created and born a male.” Because Christie’s female anatomy was “all man-made,” the court reasoned, she was not a real woman.” As a result, her marriage to Jonathon Littleton was illegal and she could not recover as his surviving spouse.